KEBEBASAN DAN KEMANDIRIAN BADAN PEMERIKSA KEUANGAN DALAM PENGAWASAN PENGGUNAAN KEUANGAN NEGARA BERDASARKAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Fery Aferio; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Management and financial responsibility of the State plays an important role in realizing the goal state, so that the founding fathers felt the need to form a special state institution which is independent, objective and free from the influence of the government to examine how the government uses the state budget approved by the House of Representatives ( DPR), such institution is the State Audit Board (BPK). One of the institutions of the State in the Constitution of the Republic of Indonesia Year 1945 is the State's financial supervisory powers stipulated in the Constitution of the Republic of Indonesia Year 1945, in article 23, letter e (1) states "To examine the financial management and responsibility of the State Audit Board held a free and independent. With the meaning of the word free and independent is expected CPC can be state institutions which can lead to the conclusion that true, objective, and critical and pro-truth and facts.The aim of this study is that the First Freedom and Independence of the State Audit Board in oversight of financial usage States under the Constitution of the Republic of Indonesia Year 1945, Second knowing Relations Working Procedures Audit Board with other institutions related to the supervision of the use of state finances by Law Law No. 15 of 2004 on the Management and State Financial Responsibility.From these results it can be concluded that the First Freedom and Independence of the CPC has been set in the 1945 Constitution in Article 23 letter e (1). The concept of freedom and kemadirian This meant that no intervention other state institutions as well as the constitutional guarantee that the work of the CPC can run optimally and objectively in accordance with the purpose of formation. The second relationship working procedures of the CPC and other state institutions, namely the House of Representatives, Parliament and the Government in order to carry out a report on the results of the examination to be followed up and taken into consideration the House if there is suspicion of a criminal act in the financial management of the country. Suggestions of Author, First expected to the government (President) and the Parliament did not intervene either in the structure of political aupun tools related to the implementation of the CPC function in each stage of the examination of the State institutions alleged to have committed irregularities use of state finances. Both are expected to be able to play its role BPK as an independent state by consolidating institutional and prioritize major cases detrimental to the State indicated in both the national and regional levels.Keywords: Freedom-Independence, The BPK.